Deep‐Red Phosphorescent Iridium(III) Complexes with Chromophoric N‐Heterocyclic Carbene Ligands: Design, Photophysical Properties, and DFT Calculations. Issue 11 (9th March 2016) - Lanoë, Pierre‐Henri; Chan, Jonny; Gontard, Geoffrey; Monti, Filippo; Armaroli, Nicola; Barbieri, Andrea; Amouri, Hani
Abstract: The synthesis of three deep‐red‐emitting iridium(III) complexes featuring a naphthalimide N‐heterocyclic carbene ligand was investigated. The introduction of this organic chromophore onto the carbene moiety changed the character of the lowest excited state from triplet metal‐to‐ligand charge transfer to triplet ligand centered, as corroborated by time‐dependent DFT calculations. All complexes displayed a naphthalimide‐based deep‐red phosphorescence emission above λ = 630 nm in polymer matrix with good quantum yields ( Φ ≈ 0.2) and long lifetimes. Abstract : Three deep‐red‐emitting Ir III complexes featuring a naphthalimide N‐heterocyclic carbene ligand are reported. Introducing this organic chromophore onto the carbene moiety changes the character of the excited state from 3 MLCT to 3 LC, as corroborated by photophysics and time‐dependent DFT. All complexes display deep‐red phosphorescence emission above 630 nm in polymer matrix with good quantum yields.